Multiple conformations of a single SNAREpin between two nanodisc membranes reveal diverse pre-fusion states - Shin, Jaeil; Lou, Xiaochu; Kweon, Dae-Hyuk; Shin, Yeon-Kyun (PORTLAND PRESS LTD, 2014)
SNAREpins must be formed between two membranes to allow vesicle fusion, a required process for neurotransmitter release. Although its post-fusion structure has been well characterized, pre-fusion conformations have been elusive. We used single-molecule FRET and EPR to investigate the SNAREpin assembled between two nanodisc membranes. The SNAREpin shows at least three distinct dynamic states, which might represent pre-fusion intermediates. Although the N-terminal half above the conserved ionic layer maintains a robust helical bundle structure, the membrane-proximal C-terminal half shows high FRET, representing a helical bundle (45 %), low FRET, reflecting a frayed conformation (39 %) or mid FRET revealing an as-yet unidentified structure (16 %). It is generally thought that SNAREpins are trapped at a partially zipped conformation in the pre-fusion state, and complete SNARE (soluble N-ethylmaleimide-sensitive factor-attachment protein receptor) assembly happens concomitantly with membrane fusion. However, our results show that the complete SNARE complex can be formed without membrane fusion, which suggests that the complete SNAREpin formation could precede membrane fusion, providing an ideal access to the fusion regulators such as complexins and synaptotagmin 1.
Keywords: MOLECULE OBSERVATION; CRYSTAL-STRUCTURE; COMPLEX; HEMIFUSION; PROTEIN; SWITCH